2009
DOI: 10.1016/j.sder.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lasers in Darker Skin Types

Abstract: The demographics of the US population continue to change at an extremely rapid pace. As of 2008, Asians, Hispanics, and African Americans accounted for 31% of the US population, and it is estimated that by the year 2050 half of the population of America will be represented by darker ethnic skin types. With the increase in the total number of individuals of skin of color, the demand for safe and effective laser therapy in darker skin types continues to increase. However, despite the increase in demand, the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…With less epidermal disruption than other lasers, the 1,064‐nm QS Nd:YAG is often safer to use on darker skinned patients. Nevertheless, the increased amount of epidermal melanin in darker skinned patients may lead to nonspecific thermal damage following laser therapy 7. This may cause adverse side effects such as blisters, crusting, transient or permanent hyper‐ or hypo‐pigmentation, textural changes, and scarring 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With less epidermal disruption than other lasers, the 1,064‐nm QS Nd:YAG is often safer to use on darker skinned patients. Nevertheless, the increased amount of epidermal melanin in darker skinned patients may lead to nonspecific thermal damage following laser therapy 7. This may cause adverse side effects such as blisters, crusting, transient or permanent hyper‐ or hypo‐pigmentation, textural changes, and scarring 1.…”
Section: Discussionmentioning
confidence: 99%
“…On histological examination, elongated dendritic dermal melanocytes are seen in the upper dermis 1. Newer treatments with the Q‐switched (QS) lasers 2–7, include the QS ruby (QSRL), 1,064‐nm QS neodymium‐doped yttrium aluminium garnet (QS Nd:YAG), and QS alexandrite (QSAL). QS lasers are often used for the treatment of pigmented lesions since they create short pulses of energy, which match the thermal relaxation time of the small particles of melanin, minimizing damage to the surrounding skin.…”
Section: Introductionmentioning
confidence: 99%
“…LHR is now well established as a form of treatment for patients with unwanted hair 4 . It is widely accepted that the long‐pulsed diode (810 nm) and long‐pulsed Nd:Yag (1064 nm) are safe for hair removal in patients with dark skin 1 …”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that not only light‐complexioned skin individuals are safely treated by LHR but dark‐skinned individuals are safely treated as well. The long‐pulsed diode (810 nm) and long‐pulsed Nd:Yag (1064 nm) are approved for hair removal in patients with dark skin 1 . However, some dark‐skinned patients are still concerned about the side effects, are simply not aware that this treatment can be performed on dark skin, or have been told by an uninformed medical provider that hair removal laser is not possible in darkly pigmented skin.…”
Section: Introductionmentioning
confidence: 99%
“…However, we resected less tissue than conventional treatments typically do, and the Q-switched lasers produce photomechanical effects that selectively target pigmented tissues. 17 Therefore, we speculate that there were no significant changes in scleral rigidity. Our previous study reported that the structure of collagen fibers is only damaged after high-energy fluence laser treatment (4 J/cm 2 ), and this damage was confined to the outer third of the sclera.…”
Section: Discussionmentioning
confidence: 85%